Activity assessment of root caries lesions with thermal and near‐IR imaging methods. Issue 3 (6th April 2016) - Lee, Robert C.; Darling, Cynthia L.; Staninec, Michal; Ragadio, Antonio; Fried, Daniel
Abstract : The purpose of this study was to evaluate thermal and near‐infrared (NIR) reflectance imaging methods for the assessment of the activity of root caries lesions. In addition, changes in the lesion structure were monitored with polarization sensitive optical coherence tomography (PS‐OCT). Artificial bovine and natural root caries lesions were imaged with PS‐OCT, and their dehydration rate was measured with thermal and NIR cameras. The lesion activity of the natural root caries samples was also assessed by two clinicians by conventional means according to ICDAS II guidelines. The thickness of the highly mineralized transparent surface layer measured using PS‐OCT increased and the area enclosed by the time‐temperature curve, Δ Q, measured with thermal imaging decreased significantly with longer periods of remineralization in simulated dentin lesions, but the NIR reflectance intensity differences, Δ I, failed to show any significant relationship with the degree of remineralization. The PS‐OCT algorithm for the automated assessment of remineralization successfully detected the highly mineralized surface layer on both natural and simulated lesions. Thermal imaging provided the most accurate diagnosis of root caries lesion activity. These results demonstrate that thermal imaging and PS‐OCT may be ideally suited for the nondestructive root caries lesion activity during a clinical examination. Abstract : The highly mineralized surface layer plays an important role in the dehydration process of remineralized dentin lesions. The PS‐OCT algorithm for the automated assessment of remineralization successfully detected the highly mineralized surface layer on root caries lesions. Thermal imaging provided the best performance in root caries lesion activity assessment. Detection of remineralization with these novel methods has the potential to aid in the clinical assessment of root caries lesion activity.